Peculiarities of direct and indirect memory of junior pupils at subsidiary schools for mentally deficient - Grigonis, A. (Psichologija, 1991)
The productivity of memory processes of mentally deficient is lower than that of pupils with normal intellect. The results of the experiments, however, revealed simultaneously that mentally deficient children are able to increase the productivity of their mnemonical activities. The productivity of indirect memory of mentally deficient pupils in all the three reproductions is considerably higher as compared to the direct memory. The grouping of the material according to its meaning-conceiving of relations that were used by the investigated is of great importance to the productivity of mnemonical activities. So semantic coding while memorizing the material increases the volume of memorizing and keeping the memorised material by children and makes its traces more constant. The facts revealed enable us to assert that children must be taught carefully and for a long time the ways of semantical treatment of the material. Experimental research enables us to think of the ways which should help to form ways memorizing for mentally deficient children. Children, learning at schools for mentally deficient, memorize the comprehended material and keep it in their memory differently. So, trying to develop mnemonical activities of the pupils, a corrective pedagogical influence is needed. Mentally deficient children add casual elements to the recalled material. Therefore ways of recalling the material, helping to correct the mentioned peculiarity, should be searched for.
Keywords: direct memory; indirenct memory; mentally deficient